Criminal justice during the long eighteenth century
1 online resource.
Keywords: This book applies three overlapping bodies of work to generate fresh approaches to the study of criminal justice in England and Ireland between 1660 and 1850. First, crime and justice are interpreted as elements of the "public sphere" of opinion about government. Second, "performativity" and speech act theory are considered in the context of the Anglo-Irish criminal trial, which was transformed over the course of this period from an unmediated exchange between victim and accused to a fully lawyerized performance. Thirdly, the authors apply recent scholarship on the history of emotions, particularly relating to the constitution of "emotional communities" and changes in "emotional regimes".